NBP Monetary Policy in 2020–2022 in the Light of Central Banks' Responses to External Shocks - Kamila Szmigiel (Finanse i Prawo Finansowe, 2025)
The purpose of the article. The aim of the article was to assess the effectiveness of monetary policy implementation under conditions of strong external shocks on the example of selected central banks and its implications for the formation of inflation expectations, taking into account the socio-demographic characteristics of selected groups of respondents.